Potensi Cendawan Antagonis Trichoderma Viride Isolat Bogor sebagai Agensi Pengendalian Hayati Penyakit Antraknosa Tanaman Cabai Merah: Antagonist Potential of Bogor Isolate of Trichoderma viride as a Biological Control Agent on Anthracnose Disease of Red Chilli - Arifin Tasrif; Dwiwanti Sulistyowati; Yuliar; Bayu Adirianto; Endang Krisnawati; Dwi Sugihati (Politeknik Pertanian Bogor, 2024)
Anthracnose disease caused by Colletottrichum capsici on chili plants that can damage yields by up to 80%. Control with fungicides has not been able to provide maximum results, because the fungus can move due to water splashes, especially in the rainy season. The use of antagonistic fungi against Colletotrichum capsici. has been widely published but is still limited to laboratory and greenhouse scales. This study aims to analyze the potential of Bogor isolate Trichoderma viride antagonist fungus against the fungus C. capsici through in-vitro study in the laboratory, screen houses, and field conditions. The experiment was structured using Complete Randomized Design (CRD) with parameters that measured respectively the antagonistic ability, and the percentage of attack by C. capsici and the severity of anthracnose disease on chili plants were both tested in screen house condition. Bogor Isolate T. viride has potential as a biological control agent for chili plants. This is proven by the ability to suppress the growth of C. capsici by 71% in vitro. The use of the fungus T. viride with a concentration of 7x106 conidia/ml (full strength) can suppress the development of anthracnose by 59 to 87% under screen house conditions. In other words, the pathogenicity of capsici in red chili plants shows a severity level of 13 to 41%.